2019
DOI: 10.1145/3336124
|View full text |Cite
|
Sign up to set email alerts
|

What Is Hard about Teaching Machine Learning to Non-Majors? Insights from Classifying Instructors’ Learning Goals

Abstract: Given its societal impacts and applications to numerous fields, machine learning (ML) is an important topic to understand for many students outside of computer science and statistics. However, machine-learning education research is nascent, and research on this subject for non-majors thus far has only focused on curricula and courseware. We interviewed 10 instructors of ML courses for non-majors, inquiring as to what their students find both easy and difficult about machine learning. While ML has a reputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…However, teaching it still is a challenge. As Sulmont et al [20] found for non‐majors at the university level, it is more difficult to teach reasoning about machine learning models than it is to teach the algorithms, yet it is possible [19]. Regarding teacher education, Zieffler et al [22] recently noted that, analogously for mathematics teachers, decision tree algorithms can be taught well in in‐service training, but the evaluation of decision trees is a greater challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, teaching it still is a challenge. As Sulmont et al [20] found for non‐majors at the university level, it is more difficult to teach reasoning about machine learning models than it is to teach the algorithms, yet it is possible [19]. Regarding teacher education, Zieffler et al [22] recently noted that, analogously for mathematics teachers, decision tree algorithms can be taught well in in‐service training, but the evaluation of decision trees is a greater challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an increasing need for wider access to A.I. learning experiences, including the development of reusable training modules and teaching A.I to non-majors (Sulmont et al, 2019;Way et al, 2016Way et al, , 2017. Even so, pedagogical challenges remain and can benefit from structured efforts such as workflow tools (WINGS) to create A.I.…”
Section: Rationalementioning
confidence: 99%
“…Even so, pedagogical challenges remain and can benefit from structured efforts such as workflow tools (WINGS) to create A.I. processes (Gil, 2016;Sulmont et al, 2019). Further, early work indicates positive motivational effects when gaming strategies are integrated into the machine learning educational experience (Wallace et al, 2010).…”
Section: Rationalementioning
confidence: 99%
“…In order to make it easier for students to learn the knowledge they want to learn, the system should have a full understanding of the three objects of teachers, students and courses, and then carry out the service in line with users' expectations. However, traditional algorithms extract specific data based on surveys and other methods, and then use fixed algorithms to analyze users and projects [1,2]. However, this method may not be able to reasonably process part of the data under certain circumstances, resulting in a large proportion of some data and affecting the service quality.…”
Section: Introductionmentioning
confidence: 99%